Building Innovative Behavior Through Training, Literacy, and Digital Communication in the General Court of West Kalimantan - Alfan Renaldi; Ake Wihadanto; Kasful Anwar (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the effect of training on innovative work behavior with digital literacy and digital communication as mediating variables in general court employees in West Kalimantan. The research method used is a quantitative approach with probability sampling techniques and sample determination using proportional random sampling. Data were collected through questionnaires distributed to 100 respondents. Data analysis used Structural Equation Modeling-Partial Least Square (SEM-PLS) with WarpPLS 7.0 software. The results showed that training had a positive and significant effect on digital literacy and digital communication. Digital literacy and digital communication also had a positive and significant effect on innovative work behavior. However, training did not have a direct effect on innovative work behavior. Digital literacy and digital communication were shown to fully mediate the effect of training on innovative work behavior. These findings emphasize the importance of effective training in improving digital literacy and digital communication of employees, which in turn encourages innovative work behavior in judicial institutions. Practical and theoretical implications are discussed further.